Mapping the path to domestic surrogacy: Identifying key facilitators and barriers in the Netherlands - Malene Tanderup; Lone Schmidt; Amrita Pande; Birgitte Bruun Nielsen; Charlotte Kroløkke; Peter Humaidan (PLoS ONE, 2025)
Background Surrogacy involves a woman who consents, before conception, to carry and deliver a child for individuals or couples unable to do so due to biological or medical limitations. This complex process encompasses medical, ethical, legal and financial considerations, resulting in varied legislation worldwide, with countries either prohibiting, restricting or legalising it. Recently, several nations have revised their legislation to encourage domestic surrogacy over international options, driven by ethical considerations and legal concerns. However, these revisions are still pending enactment. Despite the extensive literature addressing the legal, ethical, societal and medical challenges and benefits of surrogacy, no study has comprehensively analysed these factors together to fully capture the complexity of surrogacy implementation. This study aims to identify the key elements that currently facilitate the implementation of domestic surrogacy in the Netherlands and those essential elements needed for its successful continuation. Methods A qualitative case study was conducted, employing both interviews and document analysis. The selection targeted individuals who were directly involved in or had an informed perspective on handling surrogacy in the Netherlands, including healthcare professionals, healthcare system leaders, policymakers, non-governmental organisations (NGOs), academics, lawyers and counsellors and 14 experts were purposively selected. The data were analysed both inductively and deductively, using the Context and Implementation of Complex Interventions (CICI) framework to assess the contextual factors influencing the implementation of domestic surrogacy. Results Four CICI domains were identified as most influential on the implementation of surrogacy: legal (allowance of altruistic gestational surrogacy but missing legal framework on legal parentage, advertisement and payment), political (political shifts and experts’ influence, gatekeepers, intersectional collaborations), ethical (professionals’ influence on patient’s choice) and socio-cultural (donation culture and public opinion). The absence of a legal framework that secures legal parenthood, the limited availability of fertility services and the shortage of surrogate candidates represent key barriers to the implementation of domestic surrogacy in the Netherlands. Conversely, significant facilitators include extensive, well-organised collaboration between professionals and non-governmental organisations (NGOs), invited by the political system to share expert knowledge and support comprehensive legislation. Conclusion In conclusion, despite the progress achieved, domestic surrogacy remains largely inaccessible to most infertile individuals and is yet to be fully adopted. Without legal reforms, the situation of surrogacy in the Netherlands is likely to remain unchanged, mirroring the experiences of other countries with pending surrogacy legislation.